The Snapshots of Indonesian Pre-Service English Teachers’ Perspectives on Integrating Technology-Based Tools to Rural Schools - Mandasari, Berlinda; Basthomi, Yazid; Hastomo, Tommy; Afrianto; Hamzah, Intan; Aminatun, Dyah (Universitas Hamzanwadi, 2025)
Research on pre-service teachers (PSTs) has increasingly focused on their integration of technology-based tools during teaching practicums. However, limited attention has been given to how PSTs navigate these tools in rural school settings. This study examines the types of technology-based tools selected by PSTs and explores their perspectives on their use in English teaching. Employing a qualitative descriptive research design, data were collected through semi-structured interviews with eight PSTs from Universitas Teknokrat Indonesia who taught in two public rural schools during their teaching practicum. The interview data were transcribed, coded, and analyzed thematically. Findings revealed that PSTs primarily utilized AI, web-based, and game-based tools in their teaching. Among AI-based tools, ChatGPT was the most frequently used. Canva, Pinterest, and Bilibili were commonly selected for web-based tools, while Kahoot! Quizizz and Wordwall were preferred for game-based learning. PSTs expressed positive views on these tools, highlighting improvements in students’ learning satisfaction, motivation, and classroom engagement. However, they also faced challenges, particularly regarding accessibility and technical limitations in rural areas. Additionally, students had limited digital competencies, which must be addressed to prepare them for future technological advancements. Teaching obstacles also stemmed from the incompatibility of students’ digital devices, further complicating technology integration in the classroom. Despite these barriers, such challenges should not hinder the educational process. Students' limitations can be addressed through collaborative learning strategies and enhancements in instructional quality. Therefore, this study recommends infrastructure improvements to expand technology accessibility and implement adaptive teaching strategies that maximize available resources in rural settings.